2016
DOI: 10.1016/j.celrep.2016.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Two-Step Reactivation of Dormant Cones in Retinitis Pigmentosa

Abstract: Most Retinitis Pigmentosa (RP) mutations arise in rod photoreceptor genes, leading to diminished peripheral and nightime vision. Using a pig model of autosomal-dominant RP, we show glucose becomes sequestered in the retinal pigment epithelium (RPE), and thus is not transported to photoreceptors. The resulting starvation for glucose metabolites impairs synthesis of cone visual pigment -rich outer segments (OS), and then their mitochondrial-rich inner segments dissociate. Loss of these functional structures dimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
117
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(135 citation statements)
references
References 67 publications
(110 reference statements)
7
117
0
2
Order By: Relevance
“…For example, retinal genetic rescue at advanced disease stages does not lead to OS regeneration (5,18,19), suggesting a correlation between photoreceptor numbers and OS synthesis. Perhaps a critical number of rods might be needed to release glucose from RPE, where it is sequestered following rod degeneration and thus unavailable to support OS synthesis (8,20). Interestingly, in untreated RP patients (and mice), the earliest detected histopathologic change is rod OS dysgenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, retinal genetic rescue at advanced disease stages does not lead to OS regeneration (5,18,19), suggesting a correlation between photoreceptor numbers and OS synthesis. Perhaps a critical number of rods might be needed to release glucose from RPE, where it is sequestered following rod degeneration and thus unavailable to support OS synthesis (8,20). Interestingly, in untreated RP patients (and mice), the earliest detected histopathologic change is rod OS dysgenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the arrestin immunolabeling revealed dramatic dose-dependent rescue of cones-especially cone OS length. The small amount of arrestin immunolabeling in mutant retinas represents the fraction of cone cells-devoid of their OSs-that persist for some time after mutant rods have died (8).…”
Section: Significancementioning
confidence: 99%
“…While cell culture models suggest high glycolytic rates in RPE, it is thought that RPE preferentially passes glucose to the photoreceptors (Strauss, 2005). Supporting this notion, the RPE express low levels of hexokinase, which would allow glucose to pass through as opposed to entering glycolysis to be consumed in the RPE (Lowry et al, 1961; Wang et al, 2016). Kurihara et al have shown that increasing glycolytic rates in RPE may lead to photoreceptor degeneration.…”
Section: Retinal Cell-specific Metabolismmentioning
confidence: 99%
“…Another advantage of this pig model is that the inbred miniature pig genetic background facilitates the development of cell-based therapies. Researchers can inject large volumes of inoculum into the pig eye, allowing them to study the effects of cell-based therapies without any confounding effects of rejection 14 . This model has been used for several experiments, such as determining whether the dietary supplement curcumin can arrest or delay rod photoreceptor degeneration 15 .…”
Section: Retinitis Pigmentosamentioning
confidence: 99%